Proposed E-Services Quality Model and its Impact on the Indian Society (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The web technology now is a strong medium to provide information and services to the public in just a short span of time. Basically an e service provides information through the websites or web applications which can interact billions of people at a given time. This could not be possible through the traditional services and approaches. Electronic services are very famous and effective in terms of e-commerce. Type of e-service depends upon the motives of firms or organizations. The motive may differ with the objectives of the firm. For example, banking sector and e commerce organizations may provide their services to the society. Governments may provide schemes for the welfare of society with these means along with lot of benefits, such infrastructure is also a very easy to use and time consuming, so peoples are getting dependents of the e services and mobile applications, especially for the mentioned sectors  like insurance,  banking, shopping, finance, educations, real states, social media relationship, political elections, billing, entertainments, online movies, web-series, food ordering and delivery, and health sector etc.  So as people are getting used to of it, risk of cyber fraud is also increasing. As the use of online transaction has increased rapidly, especially during the lockdown and after this, peoples are dealing with e-cash rather than the cash, for this they are using either their bank accounts directly, or the e-wallets for making payment. . So hackers are doing fraud by so many ways, bank accounts and e-wallets are the prime target of them. Several cases have been reported for so far, this fraud. So there is a huge impact of the e-services and applications on the society.